Life, Scholarly Personality and the Zuhd Understanding of Büveytî, the Second Founder of the Shafiʽi School - Akdağ, Eyyup (Kalem Eğitim Kültür Akademi Derneği, 2022)
Büveytî is considered the second founder of the Shafiʽi madhhab after Imam Shafi'i himself. He was one of the most distinguished student of Imam Shafi'i with scholarly and spiritual joy. Imam Shafi'i himself appointed Büveytî as the head of the circle and announced to all his students that he would be his successor. For this reason, Büveytî is accepted as the second founding name in the madhhab after Imam Shafi’i. Imam Shafi’i also wanted the students who would not accept the leadership of Büveytî, whom he appointed to his office, to leave the circle as soon as possible. Imam Shafi'i paid attention to the vastness of Buwayti's knowledge, as well as his sensitivity about zuhd, wara‘, dhikr, and his devoted and righteous personality. After the death of Imam Shafi'i, Büveytî became the only authority within the school and Shafi'i scholars were educated by him. Shafi'i ulama who studied alongside Buwayti expanded the madhhab to a vast area, especially Buhârâ, in a short time. Büveytî was questioned in the "Mihna" events and died in prison after being subjected to severe punishment and torture for a long time because he did not accept the createdness of the Qur'an. Sufis have always had a warm interest in the Shafiʽi madhhab, considering the historical process The approaches of this madhhab on usûl and furû' were influential in the warm interest of the Sufis in Shafiism, as well as the zuhd understanding, mystical attitudes and behaviors of the important figures of the sect. In this sense, Büveytî, who is the second founding name of the sect, is an important person who came to the fore with his understanding of asceticism and his warm attitude towards the Sufis.

Büveytî, İmâm Şâfiî’nin ilmî ve manevî neşvesine sahip, en seçkin talebelerinden birisidir. İmâm Şâfiî’nin bizzat kendisi vefatına yakın bir zamanda, Büveytî’yi halkanın başına geçirmiş ve yerine halef bıraktığını tüm talebelerine ilan etmiştir. Bu manada Büveytî, İmâm Şâfiî’den sonra mezhepte ikinci kurucu isim olarak kabul edilir. İmâm Şâfiî, makamına tayin ettiği Büveytî’nin riyâsetini kabul etmeyecek talebelerin de bir an önce halkayı terk etmelerini istemiştir. İmâm Şâfiî, bu tercihinde Büveytî’nin ilminin büyüklüğünü dikkate aldığı gibi zühd, vera‘, zikir konularındaki hassasiyetini ve ibadete düşkün, sâlih kişiliğini de dikkate almıştır. İmâm Şâfiî’nin vefatından sonra Büveytî, mezhepte tek söz sahibi olmuş ve Şâfiî uleması onun eliyle yetişmiştir. Büveytî’nin tedrisinde yetişen Şâfiî uleması kısa bir zaman içinde mezhebi başta Buhârâ olmak üzere geniş bir coğrafyaya taşımışlardır. Büveytî, ömrünün son döneminde “Mihne” olaylarında sorgulanmış ve Kur’ân’ın mahlûk olduğu görüşünü kabul etmediği için ağır işkencelere maruz kalmış ve bu sebepten dolayı da vefat etmiştir. Sûfîler, tarihî süreç dikkate alındığında Şâfiî mezhebine her zaman sıcak ilgi duymuşlardır. Sûfîlerin, Şâfiliğe sıcak ilgilerinde bu mezhebin usûl ve furû‘ konusundaki yaklaşımları etkili olduğu gibi mezhebin önemli isimlerinin zühd anlayışları, tasavvufî tutum ve davranışları da etkili olmuştur. Bu manada mezhepte ikinci kurucu isim olan Büveytî, zühd anlayışı ve sûfîlere karşı sıcak tavrı ile öne çıkmış önemli bir şahsiyettir.
Keywords: Sufism; Büveytî; Shafiʽi; Mihna; Khalaq al-Qurʾan; Zuhd.; Din Araştırmaları; Tasavvuf; Büveytî; Şâfiî; Mihne; Halku’l-Kur’ân; Zühd.; Religious Studies